2019
DOI: 10.1001/jamacardio.2019.2481
|View full text |Cite
|
Sign up to set email alerts
|

Association of Region and Hospital and Patient Characteristics With Use of High-Intensity Statins After Myocardial Infarction Among Medicare Beneficiaries

Abstract: IMPORTANCE High-intensity statin use after myocardial infarction (MI) varies by patient characteristics, but little is known about differences in use by hospital or region. OBJECTIVE To explore the relative strength of associations of region and hospital and patient characteristics with high-intensity statin use after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…However, these previous studies are largely limited to a specific population, eg, patient with CHD or within a specific region, health system, or insurance plan. 12 , 25 , 26 , 27 , 28 , 29 , 30 To our knowledge, this is the first study to assess the contemporary trends in a large national cohort of patients both less than or more than age 65 years with various ASCVD types receiving care in diverse routine practice settings. The findings highlight major treatment gaps that warrant future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies are largely limited to a specific population, eg, patient with CHD or within a specific region, health system, or insurance plan. 12 , 25 , 26 , 27 , 28 , 29 , 30 To our knowledge, this is the first study to assess the contemporary trends in a large national cohort of patients both less than or more than age 65 years with various ASCVD types receiving care in diverse routine practice settings. The findings highlight major treatment gaps that warrant future study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported regional and state-level variation in both cardiovascular outcomes and practice [ 11 14 ]. Geographic variation in cardiovascular pharmacotherapy, specifically, has been described [ 15 17 ]. We sought to identify if prescribing is universally low or whether geographic variation exists in the prescribing of cardioprotective antihyperglycemic agents.…”
Section: Introductionmentioning
confidence: 99%
“… 24 , 25 In the US, adherence to similar guidance on statins was strongly associated with geography, indicating that local policy or culture plays an important role. 26 …”
Section: Discussionmentioning
confidence: 99%
“…24,25 In the US, adherence to similar guidance on statins was strongly associated with geography, indicating that local policy or culture plays an important role. 26 Previous work has shown that doctors tend to respond rapidly to safety concerns around prescribing, whereas evidencebased guidelines have less impact. 27,28 The present findings support this, showing minimal response to the 2014 guidelines, but a rapid reduction in simvastatin 40 mg in 2012, coinciding with a Medicines and Healthcare products Regulatory Agency (MHRA) drug safety alert on simvastatin >20 mg, with corresponding increases in simvastatin 20 mg and atorvastatin.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%